The use of quantitative methods in marketing : a survey of Singapore companies - Kang, Irene Pei Pei (2014)
Quantitative Methods (QM) is a scientific approach to managerial decision making. It is an important tool that can help decision makers in companies make optimal decisions and solve complex problems. As the business environment changes more rapidly and becomes more competitive, marketers are faced with the challenge to make decisions more quickly and accurately. The usefulness of QM in making marketing decisions thus becomes more evident. The objective of this study is to determine the extent and nature of QM usage in marketing by Singapore companies. A questionnaire survey was sent to 170 Singapore companies. The survey results showed that the usage of QM in marketing was not widespread. However, the authors felt that usage would increase in the future. This was because the majority of the user companies indicated that their future usage of quantitative methods would increase whereas half of the non user companies indicated that they would use QM in the future. QM usage in marketing among Singapore companies could be increased through promoting greater awareness of the usefulness of QM and also through training marketing decision makers in the use of the various quantitative techniques. With these and the increasing complexity of Singapore’s business environment, the prospect of greater QM usage would indeed be bright.